2016
DOI: 10.7205/milmed-d-15-00473
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Deploying in Support of the U.S. Response to Ebola: A Systematic Review and Meta-Analysis of Past Outbreaks

Abstract: Deployed service members may return with clinically significant problems, the most notable of which is depression. Delivering resilience training and fostering altruistic acceptance may protect service members from developing mental health disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
3
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 49 publications
2
82
3
13
Order By: Relevance
“…Caring for patients during an epidemic/pandemic may impact negatively on the mental health of HCPs [5,6]. While studies on this impact exist, this literature has yet to be updated and fully synthesized alongside a review of potential risk and protective factors.…”
Section: Why Is This Review Needed?mentioning
confidence: 99%
“…Caring for patients during an epidemic/pandemic may impact negatively on the mental health of HCPs [5,6]. While studies on this impact exist, this literature has yet to be updated and fully synthesized alongside a review of potential risk and protective factors.…”
Section: Why Is This Review Needed?mentioning
confidence: 99%
“…Research during the H1N1 outbreak in 2009 (24) , found out that the average rate of psychological distress among exposed health professionals was nearly 40%. According to a systematic review (25) , risk factors for psychological distress during an epidemic included the duration of exposure (26) , little professional experience (26) , being single (27) , nurse (28) , a part-time job (28) , female (29) , physical health problem (29) , difficulty in carrying out activities due to precaution measures (28) and absence of psychological support at work (29) .…”
Section: The Emotions Of Health Professionals In the Battle Against Cmentioning
confidence: 99%
“…Health professionals who experienced working directly with infected patients had relatively high levels of depressive symptoms one year after the outbreak. Insomnia, alcohol and other drug abuse, PTSD symptoms, depression and anxiety have also been reported (25) . All these factors require caution in evaluation, because of the effects on the quality of life of professionals.…”
Section: The Post-epidemic Consequences For the Mental Health Of Healmentioning
confidence: 99%
“…The seven items were summed, resulting in a composite score ranging from 0 to 28. The summed scores were categorized to include no sleep problems (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22-28) based on validated literature guidelines (54). The scale was further dichotomized to no sleep problems (0-14) and sleep problems (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Behavioral Health and Wellbeingmentioning
confidence: 99%
“…Several previous studies have focused on stressors and behavioral health consequences experienced by medical staff responding to outbreaks of infectious disease, such as Middle East Respiratory Syndrome(1), Severe Acute Respiratory Syndrome (2), Ebola (3,4) and . Medical professionals like physicians and nurses managing these outbreaks report elevated psychological distress (5,(8)(9)(10), posttraumatic stress symptoms (2,(8)(9)(10)(11), depression and anxiety (4)(5)(6)9), sleep problems (5,6,9), and burnout (7,8). Studies have also documented that working in the context of an outbreak can place a strain on the team as a whole (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%